Knowledge Sharing, Absorptive Capacity and Innovation Capabilities: An Empirical Study on Small and Medium Enterprises in North Sulawesi, Indonesia - Nikolas Fajar Wuryaningrat (Gadjah Mada International Journal of Business, 2013)
The capability of a firm to instill innovation depends on its knowledge resources. This capability can be utilized by facilitating knowledge sharing and absorptive capacity in the context of small and medium enterprises. The purpose of this research is to examine how knowledge sharing can be transformed into innovation capabilities. Research suggests that knowledge sharing will first influence absorptive capacity before knowledge can be transformed to innovation capabilities. This research was conducted in North Sulawesi which has excellent economic growth by involving small and medium enterprises. The results show that knowledge donating and knowledge collecting positively influence SME’s innovation capabilities if absorptive capacity is also developed. In other words, the result of the research gives us empirical evidence that new knowledge created from knowledge sharing can be transformed into innovation capabilities if it is supported by higher absorptive capacity.